Beyond the dinosaurs : monsters of the air and sea - Brown, Charlotte Lewis; Wilson, Phil, 1948- (New York : HarperCollins, 2007)
Illustrations and simple text introduce young readers to the characteristics and habits of eleven prehistoric dinosaurs.
Pteranodon -- Deinosuchus -- Elasmosaurus -- Ichthyosaurus -- Mosasaurus -- Hainosaurus -- Pterodaustro -- Microraptor -- Kronosaurus -- Placodus -- Archaeopteryx.
"2, reading with help."
2.8
K-3
Keywords: Reptiles, Fossil -- Juvenile literature; Animals, Fossil -- Juvenile literature; Reptiles, Fossil; Prehistoric animals; Fossil reptiles; Prehistoric animals